Gender-related differences in the association between serum uric acid and left ventricular mass index in patients with obstructive hypertrophic cardiomyopathy. Issue 1 (December 2016) - Zhang, Changlin; Liu, Rong; Yuan, Jiansong; Cui, Jingang; Hu, Fenghuan; Yang, Weixian; Zhang, Yan; Yang, Chengzhi; Qiao, Shubin
Abstract Background Serum uric acid (SUA) is associated with left ventricular hypertrophy in a wide spectrum of study population. However, whether this association exists in patients with hypertrophic cardiomyopathy (HCM, including obstructive HCM), and if present, whether gender has any impact on this association, remains unknown. Methods A total of 161 patients with obstructive HCM (age 47.2 ± 10.8 years, 99 (62 %) men) were included in this study. All patients underwent extensive clinical, laboratory, echocardiographic, and cardiac magnetic resonance (CMR) imaging examinations. Left ventricular mass index (LVMI) was assessed using CMR. Results The mean value of SUA was 353.4 ± 87.5 μmol/L. Both SUA levels (381.2 ± 86.4 vs. 309.0 ± 69.3 μmol/L, p < 0.001) and LVMI (96.2 ± 32.1 vs. 84.4 ± 32.4 g/m2, p = 0.025) were significantly higher in men than in women. LVMI increased progressively across sex-specific tertiles of SUA in women (p = 0.030), but not in men (p = 0.177). SUA was positively correlated with LVMI in female patients (r = 0.372, p = 0.003), but not in males (r = 0.112, p = 0.269). On multivariate linear regression analysis, SUA was independently associated with LVMI in females (β = 0.375, p = 0.002), but not in males. Conclusions SUA levels are significantly and independently associated with LVMI in women with obstructive HCM, but not in men. Our findings imply the potential significance of urate-lowering regimens in female patients with obstructive HCM.